The Web as weapon [cyber warfare]. - Kumagai, J. (IEEE spectrum)
As tensions in the Middle East erupted into vicious street fighting at the end of 2000, a different sort of pitched battle was being waged behind the scenes. With all the fervor of their comrades in arms, computer-savvy patriots on both sides managed to infiltrate or disable enemy Web servers. The prospect of cyber warfare, or information warfare, is a deadly serious matter in military circles. The more heavily we come to rely on computer networks, the greater the fear that adversaries will attack the networks themselves. In the very worst case-what some have termed an electronic Pearl Harbor-a sudden, all-out network assault would knock out communications as well as financial, power, transportation, military, and other critical infrastructures, resulting in total societal collapse. The author discusses the issues raised by cyber warfare and protection of vital information systems